2013
DOI: 10.5455/ijmsph.2013.2.247-251
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices about cervical cancer and screening among nursing staff in a teaching hospital

Abstract: Background: Estimated cervical cancer screening practice is very low and load of cases very high in India. The studies document that nurses play a crucial role of enlightening community about need and availability of Pap smear. It is important therefore to understand the perceptions and practices of nurses about cervical cancer and screening. Aims & Objective: To evaluate the Knowledge Attitude & Practices (KAP) of the Nurses on cervical cancer and screening. Material and Methods: A self-administered, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 6 publications
10
31
4
Order By: Relevance
“…Majority of the nurses didn't knew about the other risk factors like young age at first intercourse (12.9%), cigarette smoking (15.9%), high parity (9.4%) and low socioeconomic status (12.9%) are risk factors for cancer cervix. This is in accordance with the study done by Goyal A et al 15 in Surat, India where 61.5% and 44% knew multiple sexual partners and intercourse at early age as risk factors but only 12% and 3.5% knew about contraception and smoking as risk factors. These were also in accordance to the study done by Ali SF et al 13 where 45% of the participant knew promiscuity as risk factor for cervical cancer but other risk factors were lesser known.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Majority of the nurses didn't knew about the other risk factors like young age at first intercourse (12.9%), cigarette smoking (15.9%), high parity (9.4%) and low socioeconomic status (12.9%) are risk factors for cancer cervix. This is in accordance with the study done by Goyal A et al 15 in Surat, India where 61.5% and 44% knew multiple sexual partners and intercourse at early age as risk factors but only 12% and 3.5% knew about contraception and smoking as risk factors. These were also in accordance to the study done by Ali SF et al 13 where 45% of the participant knew promiscuity as risk factor for cervical cancer but other risk factors were lesser known.…”
Section: Discussionsupporting
confidence: 78%
“…If detected early 71.5% of them reported it to be curable. Similarly in the study by Goyal A et al 15 approximately 70% participants believed that cancer cervix is curable if detected early. Pap smear was recognized as major screening technique by 74% participants.…”
Section: Discussionmentioning
confidence: 98%
“…In general, though they heard about cervical cancer and its screening methods, they did not have indepth knowledge about it. The awareness about Pap smear in our study is similar to the findings of Goyal et al, and Orantaphan et al, 22,25 Mutambara et al, reported that women had high knowledge about the nature of a Pap smear test, and they also knew that cancer was the second highest killer of women compared to HIV. The participants were aware that if early interventions were made, treatment could reduce the chances of disease progression 26 .…”
Section: Resultssupporting
confidence: 81%
“…Some of the very important symptoms of cervical cancer are vaginal bleeding after sexual intercourse and vaginal bleeding after menopause, very few of the subjects knew about these symptoms. The majority of the subjects were aware of the symptoms pelvic pain and postmenopausal bleeding which is similar to other reports by Ahmed et al, and Alok et al, 21,22 The women who have ever heard of cervical cancer were asked if they knew of any method that could prevent the disease. Among the total subject who could identify the major correct answer was 79.7% it is possible to prevent it, 82.1% early detection increase survival, 60.2% it is preventable but only 17.5% knew about vaccination against HPV.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation